Comparative analysis of clinical, physiological, temperamental and personality characteristics of elderly subjects and young subjects with asthma - Panek, Michał G. (PLoS One, 2020)
BACKGROUND: Asthma is a heterogeneous disease of a complex etiology in which genetic, environmental and personality variables are important factors determining the development of complicated strategies related to coping with stress and temperament traits. Our thesis is that coping styles in asthmatic patients are modified by the environment (chronic inflammation and stress) which affects individual temperament traits in the course of time. Thus, patient age is one of factors which determine the clinical image of asthma and its natural history. AIM: The aim of the study was to evaluate the variables describing stress coping styles and temperament in young (18 to 35 years old) and elderly asthmatics (aged ≥60 years). MATERIAL AND METHODS: A total of 200 patients, 104 elderly and 96 young asthmatics were enrolled in the study. Apart from medical examination, the following tests were performed in all subjects: the Formal Characteristics of Behavior- Temperament Inventory (FCB-TI), Coping Inventory for Stressful Situations (CISS), Beck Depression Inventory, State-Trait Anxiety Inventory, and Borg Rating of Perceived Exertion (RPE) Scale. RESULTS: Elderly patients with asthma exhibited higher intensity of anxiety as a trait, a higher level of depression and experienced dyspnea, as well as higher levels of stress coping strategies such as Avoidance-Oriented Coping (AOC), Distraction Seeking (DS) and Social Diversion (SD) compared to young asthmatics. In elderly patients, Perseverance and Sensory Sensitivity traits have been observed to decline with the duration and development of asthma at later life stages as opposed to young asthmatics, in whom these temperament characteristics are elevated. CONCLUSIONS: Asthma is a heterogeneous disease of a complex etiopathogenesis that has a complex interplay with mental health. The present study confirms a relationship between age and stress coping strategies as well as temperament traits.